2021
DOI: 10.48048/wjst.2021.6541
|View full text |Cite
|
Sign up to set email alerts
|

Energy Fluxes and Evapotranspiration in a Rubber Agroecosystem of the Southern Thailand

Abstract: Evapotranspiration (ET) plays an important role in land surface atmosphere interaction which significantly drives hydrological cycle, vegetation functioning resulting to agricultural production. In this study, observations of energy fluxes, energy partitioning, and evapotranspiration (ET) were conducted on a monoclonal stand of rubber trees (Hevea brasiliensis) plot (clone RRIM 600) in 2017. The forestry population was 17 years old and had been tapped continuously over 10 years for latex harvesting at the Rubb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…The rubber plantation is one of the native species in the tropical forest in Amazonia, with its successful introduced in Southeast Asia in the late 19th century, it has been a major economic plantation in the locality. The rubber plantation generally consumes about 72% of net radiation for evapotranspiration (Giambelluca et al, 2016;Pierret et al, 2016;Ruairuen et al, 2021), which raises concerns about water security in the plantation region (Tan et al, 2011;Niu et al, 2019). Studies have demonstrated that atmospheric dryness, rather than soil water is the major driver leading to canopy evaporation during drought season (Sopharat et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The rubber plantation is one of the native species in the tropical forest in Amazonia, with its successful introduced in Southeast Asia in the late 19th century, it has been a major economic plantation in the locality. The rubber plantation generally consumes about 72% of net radiation for evapotranspiration (Giambelluca et al, 2016;Pierret et al, 2016;Ruairuen et al, 2021), which raises concerns about water security in the plantation region (Tan et al, 2011;Niu et al, 2019). Studies have demonstrated that atmospheric dryness, rather than soil water is the major driver leading to canopy evaporation during drought season (Sopharat et al, 2015).…”
Section: Introductionmentioning
confidence: 99%